Warm Ambient Temperature Decreases Food Intake in a Simulated Office Setting: A Pilot Randomized Controlled Trial - Bernhard, Molly C.; Li, Peng; Allison, David B.; Gohlke, Julia M. (Frontiers in Nutrition, 2015)
Background: We hypothesized that exposure to temperatures above the thermoneutral zone would decrease food intake in young adults in a sedentary office environment over a 2-hour period. Methods: Participants wearing standardized clothing were randomized to perform routine office work in either within the thermoneutral zone, considered control (19-20°C), or above the thermoneutral zone considered warmer (26-27°C) treatment in parallel-group design (n=11 and 9, respectively). Thermal images of the inner canthus of their eye and middle finger nail bed, representing proxies of core and peripheral temperatures, respectively, were taken at baseline, 1st, and 2nd hour during this lunchtime study. Relative heat dissipation was estimated as peripheral temperature. General linear models were conducted to examine the effects of thermal treatment the calories intake and potential mediation. Researchers conducted the trial registered as NCT02386891 at Clinicaltrials.gov during April- May 2014. Results: During the 2 hours stay in different ambient temperatures, the participants in the control conditions ate 99.5 kcal more than those in the warmer conditions; however, the difference was not statistically significant. Female participants ate about 350 kcal less than the male participants (P=0.024) in both groups and there was no significant association between calories intake and participant’s BMI. After controlling for thermal treatment, gender and BMI, the participant’s peripheral temperature was significantly associated with calories intake (p=0.002), suggesting a mediating effect. Specifically, for every 1°C increase in peripheral temperature indicating reduced heat dissipation, participants ate 85.9 kcal less food. Conclusions: This pilot study provided preliminary evidence of effects of thermal environment on food intake and the decreased food intake in the experimental (warmer) environment is potentially mediated through thermoregulatory mechanisms.